Influence of forest configuration and bird exclusion on insect herbivory in Indonesian oil palm smallholdings (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pradana DH, Winarni NL, Patria MP, Yasman. 2025. Influence of forest configuration and bird exclusion on insect herbivory in Indonesian oil palm smallholdings. Biodiversitas 26: 4640-4646. The insect pest control services provided by birds may help address one biological challenge in oil palm plantations. Previous studies suggest that understory birds contribute to this ecosystem service and that forest configuration may influence their effectiveness. We investigated whether understory birds reduce insect pests and whether forest configuration affects their pest control services in six oil palm smallholdings in Indonesia. Understory birds were surveyed using the point count method at 0-200 m from adjacent forests. Herbivory rates, used as a proxy for insect pest activity, were assessed through a bird enclosure experiment. The indirect bird effect on herbivory rate was also evaluated using this experiment. We used binomial Generalized Linear Mixed Model (GLMM) to analyze the effects of understory bird abundance and forest configuration on herbivory rates. Results showed the herbivory rate ranged from 0.01 to 0.84 mm². A weak negative relationship between understory bird abundance and herbivory in control treatments (z: -1.65, n: 12, p-value
Keywords: Forest configuration, herbivory rate, insect pest control, oil palm smallholdings, understory birds